Estimate of the environment impact of the ELT instrument MOSAIC - Janssen, A; El Hadi, K; Bharmal, NA; Dalton, G; Rodrigues, M (Society of Photo-optical Instrumentation Engineers, 2024)
MOSAIC is an instrument for the Extremely Large Telescope (ELT). The instrument has started phase B, and apart from technical and financial requirements, MOSAIC has the additional requirement to investigate and minimise its environmental impact. The first step is to estimate the carbon footprint (and other effects) in a ‘Life Cycle Analysis’, for the instrument development up to Provisional Acceptance in Chile. This paper presents a preliminary analysis, aimed at identifying potential contributors to environmental impact. Investigated contributors are: materials, Full-Time-Equivalents, travel, and transport of the instrument. Not yet investigated (due to lack of information or certainty) are: electronics, test facilities and prototyping. Uncertainty in input data and conversion factors leads to error bars of a factor 2 or larger. Therefore, the outcome of the analysis can be used for internal comparison of contributors only, and it should not be used for comparison to other instruments or disciplines.